ANALISIS PENGENDALIAN SOSIAL KONFLIK SISWA ETNIK MELAYU DAN TIONGHOA DI SMPN 2 SUNGAI RAYA - Todi, Petrus; Bahari, Yohanes; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research tittle is an analysis of social conflict control among the malay and Chinese students in SMP N 2 Sui raya kep. The problem in this research is how does the social control by the school in controling the conflict among the malay and Chinese students in SMP N 2 SUI KEP. How does the social control result that has been done by the school in controlling the social conflict among the malay and Chinese students in SMP N 2 SUI KEP?.  The form of this research is qualitative study which using descriptive methodology. the technique in collecting the data is observation guide, interview guide, and documentation. The result of this research shows that the moral values cultivated by the school are good. Trough the politeness cultivating, respecting each ethnics, tolerance each religion, honestly and always carrying each other, also carrying of the environment.                Keywords: Chinese, Malay, Social, Conflict, Control.